The Jossey-Bass handbook of nonprofit leadership and management - Renz, David O. (David Owen); Herman, Robert D., 1946- (San Francisco, CA : Jossey-Bass, 2010)
"This is the Third Edition of the bestselling nonprofit management reference and text called the "big green book." Based on updated research, theory, and experience, this comprehensive edition offers practical advice on managing nonprofit organizations and addresses key aspects such as board development, strategic planning, lobbying, marketing, fundraising, volunteer management, financial management, risk management, and compensation and benefits. New chapters cover developments in such areas as social entrepreneurship, financial leadership and capital structure, accountability and transparency, and the changing political-legal climate. It includes an instructor's manual."--
Historical perspectives on nonprofit organizations in the United States / Peter Dobkin Hall -- The legal framework of the nonprofit sector in the United States / Bruce R. Hopkins and Virginia C. Gross -- The changing context of nonprofit leadership / Lester M. Salamon -- The many faces of nonprofit accountability / Alnoor Ebrahim -- Leadership, governance, and the work of the board / David O. Renz -- Executive leadership / Robert D. Herman -- Ethical nonprofit management : core values and key practices / Thomas H. Jeavons -- Strategic management / William A. Brown -- Strategic planning and the strategy change cycle / John M. Bryson -- Social entrepreneurship and social enterprise / Matthew T.A. Nash -- Marketing for nonprofit organizations / Brenda Gainer -- Strategic communications / Kathy Bonk -- Advocacy, lobbying, and social change / Marcia Avner -- Collaboration and strategic alliances / John A. Yankey and Carol K. Willen -- Outcome assessment and program evaluation / John Clayton Thomas -- Evaluating the effectiveness of nonprofit organizations / Vic Murray -- Financial leadership in nonprofit organizations / Jeanne Bell -- Nonprofit finance : developing nonprofit resources / Dennis R. Young -- Designing and managing the fundraising program / Robert E. Fogal -- Social enterprise and nonprofit ventures / Scott T. Helm -- Managing the challenges of government contracts / Steven Rathgeb Smith -- Financial management and accounting / David W. Young -- Risk management / Melanie Lockwood Herman -- Effective human resource practices : recruitment and retention in nonprofit organizations / Mary R. Watson and Rikki Abzug -- Total rewards programs in nonprofit organizations / Nancy E. Day -- Designing and managing volunteer programs / Jeffrey L. Brudney -- The future of nonprofit leadership and management / David O. Renz.
Includes bibliographical references and indexes.
Keywords: Nonprofit organizations -- Management